1991
DOI: 10.1111/j.1365-2788.1991.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff perceptions of sadness among people with mental handicaps

Abstract: This study investigated the use of an informant behaviour checklist to examine carestaff perceptions of sadness among a hospital population of people with mental handicaps. Using Cohen's kappa statistic there were only three checklist items which had acceptable levels of inter-rater agreement (physical aggression, crying and verbal abuse) with no significant variation in the incidence of those behaviours according to the severity of mental handicap. The flndings suggest that future research might attend to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Subsequent studies using this checklist by Tsiouris, Mann, Patti, and Sturmey (2004) and a similar empirical study by Ross and Oliver (2003a) found no relationship between measures of mood and maladaptive behaviors. Clarke, Reed, and Sturmey (1991) found that staff had considerable difficulty identifying when people with ID were sad, which might explain why no relationship was observed in these studies. Ross and Oliver's (2003b) subsequent review suggested that the literature on identification of mood symptoms in people with severe and profound ID is marked by problems with reliability and validity, as well as conceptual problems in identifying when a maladaptive behavior may be a behavioral equivalent of depression.…”
Section: Behavioral Equivalentsmentioning
confidence: 80%
“…Subsequent studies using this checklist by Tsiouris, Mann, Patti, and Sturmey (2004) and a similar empirical study by Ross and Oliver (2003a) found no relationship between measures of mood and maladaptive behaviors. Clarke, Reed, and Sturmey (1991) found that staff had considerable difficulty identifying when people with ID were sad, which might explain why no relationship was observed in these studies. Ross and Oliver's (2003b) subsequent review suggested that the literature on identification of mood symptoms in people with severe and profound ID is marked by problems with reliability and validity, as well as conceptual problems in identifying when a maladaptive behavior may be a behavioral equivalent of depression.…”
Section: Behavioral Equivalentsmentioning
confidence: 80%
“…For example, there is evidence that mood can be judged reliably and, to some extent, validly for people with severe disabilities (Green et al 2005) but this is often described as requiring very careful operationalization of individual presentations. If observers are not carefully trained then there can be significant degrees of inconsistency in carer's reports (Clark et al 1991). Given the difficulties in this area there are surprisingly few studies of the reliability of diagnosis of mental ill-health for people with intellectual disabilities (Cooper et al 2003).…”
Section: The Reliability Of Diagnosis Of Mental Ill-health In People mentioning
confidence: 99%
“…2005) but this is often described as requiring very careful operationalization of individual presentations. If observers are not carefully trained then there can be significant degrees of inconsistency in carer’s reports (Clark et al. 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For example, among people with and without mental handicaps, happiness has been found to be more easily recognised than other emotional states (Maurer & Newbrough, 1987a;Ekman, 1982;Gray, Fraser & Leudar, 1983). Although in one study care staff claimed to be able to identify sadness in clients with mental handicaps, inter-rater agreement on its behavioural indicators was low (Clark, Reed & Sturmey, 1991). Of course, encoding success in communicating emotions is dependent on decoder sensitivity.…”
Section: Introductionmentioning
confidence: 99%